104 The Assessment of the Clinical Frailty Scale in Emergency Department (Quality Improvement Project). (28th February 2022) - Aung, M.; Khalil, A.; Abdelaal, M.
Abstract: Aim: To enforce clinicians to use clinical frailty scale (CFS) in the elderly population which can guide the management pathway i.e., suitable for ITU admission or surgical intervention Method: As part of the QIP, an audit was carried out which looked at two criteria: CFS used at Emergency Department triage, or any first point of contact with acute care (including paramedics), alongside Early Warning Scores. CFS used (when appropriate) to assess baseline health and inform discussions on treatment expectations The above criteria are based on NICE guidelines NG191 and the specialized Clinical Frailty Network website. The inclusion criteria are patients older than 80 years of age. The first cycle looks at 50 randomized patients presented to A&E in July 2021, followed by the implementation of change. The target for all criteria is 75%. The second cycle looks at 50 randomized patients presented to A&E in August 2021. Results: Initial audit data suggests the following: Crit 1: 40% Crit 2: 2% This suggests we are performing less than the national standard. Therefore, an implementation that involves a change in a software system, poster and teaching session was done. This approach improves our performance immensely. Crit 1: 100% (now mandatory due to software system i.e., sustainable change) Crit 2: 40% The third cycle was currently underway with a plan to undertake CFS awareness month. Conclusions: This QIP helps not only the emergency team but also admission teams particularly ITU and surgical speciality to reach the management decision for the elderly population.